(untitled) (Journal of Contemporary Educational Policies and Practices, 2021)
Higher education institutions (HEIs) are under pressure to provide evidence of student success. In addition to traditional performance indicators such as GPA, grades, and rates of retention, graduation and employment, stakeholders also required institutions to provide evidence of institutional learning outcomes (ILOs). ILOs encompass the knowledge and skills that all students regardless of disciplines from a specific university are expected to demonstrate upon their graduation. This case study examines a complete internal quality assurance (IQA) cycle from a U.S. comprehensive university, including the adaptation of national authentic assessment measures, the use of technology in data analysis, the best practices to communicate assessment results to multiple internal stakeholders to facilitate leadership decision-making, the challenges encountered, and the improvement plans to sustain the procedure. Researchers also make recommendations to Vietnam HEIs that want to adopt IQA of ILOs for both quality improvement and accountability purposes.